Respuestas
Respuesta dada por:
1
1.)
![{log_4(x-6)=3}\\{log_4(x-6)=log_4(64)}\\{x-6=64}\\{x=6+64}\\{x=70} {log_4(x-6)=3}\\{log_4(x-6)=log_4(64)}\\{x-6=64}\\{x=6+64}\\{x=70}](https://tex.z-dn.net/?f=%7Blog_4%28x-6%29%3D3%7D%5C%5C%7Blog_4%28x-6%29%3Dlog_4%2864%29%7D%5C%5C%7Bx-6%3D64%7D%5C%5C%7Bx%3D6%2B64%7D%5C%5C%7Bx%3D70%7D)
2.)
![{log_6(x^2-2)=2}\\{log_6(x^2-2)=log_6(36)}\\{x^2-2=36}\\{x^2=36+2}\\{x^2=38}\\{x= \sqrt{38} } {log_6(x^2-2)=2}\\{log_6(x^2-2)=log_6(36)}\\{x^2-2=36}\\{x^2=36+2}\\{x^2=38}\\{x= \sqrt{38} }](https://tex.z-dn.net/?f=%7Blog_6%28x%5E2-2%29%3D2%7D%5C%5C%7Blog_6%28x%5E2-2%29%3Dlog_6%2836%29%7D%5C%5C%7Bx%5E2-2%3D36%7D%5C%5C%7Bx%5E2%3D36%2B2%7D%5C%5C%7Bx%5E2%3D38%7D%5C%5C%7Bx%3D+%5Csqrt%7B38%7D+%7D)
3.)
![{log_3(x^2+x+3)=2}\\{log_3(x^2+x+3)=log_3(9)}\\{x^2+x+3=9}\\{x^2+x-6=0}\\{(x+3)(x-2)=0}\\\\{x-2=0 }\\{x=2}\\\\{x+3=0}\\{x=-3} {log_3(x^2+x+3)=2}\\{log_3(x^2+x+3)=log_3(9)}\\{x^2+x+3=9}\\{x^2+x-6=0}\\{(x+3)(x-2)=0}\\\\{x-2=0 }\\{x=2}\\\\{x+3=0}\\{x=-3}](https://tex.z-dn.net/?f=%7Blog_3%28x%5E2%2Bx%2B3%29%3D2%7D%5C%5C%7Blog_3%28x%5E2%2Bx%2B3%29%3Dlog_3%289%29%7D%5C%5C%7Bx%5E2%2Bx%2B3%3D9%7D%5C%5C%7Bx%5E2%2Bx-6%3D0%7D%5C%5C%7B%28x%2B3%29%28x-2%29%3D0%7D%5C%5C%5C%5C%7Bx-2%3D0+%7D%5C%5C%7Bx%3D2%7D%5C%5C%5C%5C%7Bx%2B3%3D0%7D%5C%5C%7Bx%3D-3%7D)
4.)
![{log_2(x^2-x+14)=4}\\{log_2(x^2-x+14)=log_2(16)}\\{x^2-x+14=16}\\{x^2-x-2=0}\\{(x-2)(x+1)=0}\\\\{x-2=0 }\\{x=2}\\\\{x+1=0}\\{x=-1} {log_2(x^2-x+14)=4}\\{log_2(x^2-x+14)=log_2(16)}\\{x^2-x+14=16}\\{x^2-x-2=0}\\{(x-2)(x+1)=0}\\\\{x-2=0 }\\{x=2}\\\\{x+1=0}\\{x=-1}](https://tex.z-dn.net/?f=%7Blog_2%28x%5E2-x%2B14%29%3D4%7D%5C%5C%7Blog_2%28x%5E2-x%2B14%29%3Dlog_2%2816%29%7D%5C%5C%7Bx%5E2-x%2B14%3D16%7D%5C%5C%7Bx%5E2-x-2%3D0%7D%5C%5C%7B%28x-2%29%28x%2B1%29%3D0%7D%5C%5C%5C%5C%7Bx-2%3D0+%7D%5C%5C%7Bx%3D2%7D%5C%5C%5C%5C%7Bx%2B1%3D0%7D%5C%5C%7Bx%3D-1%7D)
5.)
![{log_3(x^2+x+15)=3}\\{log_3(x^2+x+15)=log_3(27)}\\{x^2+x+15=27}\\{x^2+x-12=0}\\{(x+4)(x-3)=0}\\\\{x+4=0 }\\{x=-4}\\\\{x-3=0}\\{x=3} {log_3(x^2+x+15)=3}\\{log_3(x^2+x+15)=log_3(27)}\\{x^2+x+15=27}\\{x^2+x-12=0}\\{(x+4)(x-3)=0}\\\\{x+4=0 }\\{x=-4}\\\\{x-3=0}\\{x=3}](https://tex.z-dn.net/?f=%7Blog_3%28x%5E2%2Bx%2B15%29%3D3%7D%5C%5C%7Blog_3%28x%5E2%2Bx%2B15%29%3Dlog_3%2827%29%7D%5C%5C%7Bx%5E2%2Bx%2B15%3D27%7D%5C%5C%7Bx%5E2%2Bx-12%3D0%7D%5C%5C%7B%28x%2B4%29%28x-3%29%3D0%7D%5C%5C%5C%5C%7Bx%2B4%3D0+%7D%5C%5C%7Bx%3D-4%7D%5C%5C%5C%5C%7Bx-3%3D0%7D%5C%5C%7Bx%3D3%7D)
Salu2. :)
2.)
3.)
4.)
5.)
Salu2. :)
Anónimo:
Muchas Gracias , me ayudò muchisimo !!! . Geniales las respuestas !!
Preguntas similares
hace 9 años
hace 9 años
hace 9 años
hace 9 años